CGIAR Research Program on Policies, Institutions, and Markets - Plan of Work and Budget 2019 - CGIAR Research Program on Policies, Institutions, and Markets (CGIAR Research Program on Policies, Institutions, and Markets, 2019)
The plans for 2019 have a strong focus on syntheses of the work conducted in the first three years of Phase 2, to disseminate lessons learned on extension methods, youth employment in Africa, mechanization, gender outcomes in social protection programs, multi-stakeholder platforms for natural resource governance, and gender transformative approaches. Collaborations with other CRPs will include a CGIAR Foresight Report, a Gender and Agriculture Report, and research on seed systems, value chains, and land restoration.